1991
DOI: 10.1111/j.1432-1033.1991.tb16023.x
|View full text |Cite
|
Sign up to set email alerts
|

Multisite contacts involved in coupling of the β‐adrenergic receptor with the stimulatory guanine‐nucleotide‐binding regulatory protein

Abstract: Synthetic peptides, 12 -22 amino acid residues long, comprising the presumed coupling sites of the p-adrenergic receptor with the stimulatory guanine-nucleotide-binding regulatory protein (G,), were examined for their ability to modulate G, activation in turkey erythrocyte membranes. Three peptides corresponding to the second cytoplasmic loop, the N-terminal region of the third cytoplasmic loop, and the N-terminal region of the putative fourth cytoplasmic loop, compete synergistically with the hormone-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 31 publications
4
50
0
1
Order By: Relevance
“…Our observation that three different competing peptides affect AT "A R-G-protein coupling is consistent with the hypothesis that multiple regions of the receptor form a three-dimensional binding surface to which the G-protein is coupled [8,14,28]. In the AT "A R, this binding surface comprises at least regions from i2, i3 and the C-terminal tail.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our observation that three different competing peptides affect AT "A R-G-protein coupling is consistent with the hypothesis that multiple regions of the receptor form a three-dimensional binding surface to which the G-protein is coupled [8,14,28]. In the AT "A R, this binding surface comprises at least regions from i2, i3 and the C-terminal tail.…”
Section: Discussionsupporting
confidence: 89%
“…This juxtamembranous domain has a highly charged lysine-rich sequence, which, like the N-terminal region of i2, is predicted to form an amphiphilic helix. In fact, CD and NMR analysis of AT "A R peptide 300-320 has shown that this peptide, which is very similar to the one used in the present study, does form an amphipathic α-helix [27] and suggests that the helix-to-coil transition in i o is a mechanism by which G-proteins associate or dissociate from the AT "A R. In β-adrenergic receptors, peptide competition studies have shown that a similar lysine-rich amphiphilic helix in the proximal C-terminal tail plays a critical role in receptor-G s -protein coupling [8]. Palmitoylation of cysteine-322 in the C-terminal tail of the β-adrenergic receptors is speculated to form a short intracellular loop by embedding the palmitoyl moiety in the membrane.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations